Specific PCR‐based detection of Phomopsis heveicola the cause of leaf blight of Coffee (Coffea arabica L.) in China. (1st April 2021) - Lu, Y.; Wu, W.H.; He, C.P.; Liang, Y.Q.; Huang, X.; Zheng, J.L.; Xi, J.G.; Tang, S.B.; Yi, K.X.
Abstract: Coffee ( Coffea arabica L.) is currently grown in many tropical and subtropical areas countries and is a major traded commodity for the developing world. Coffee leaf blight, caused by Phomopsis heveicola, is one of the most important fungal diseases dangerous to coffee crops in China. This study aimed to develop a PCR‐based diagnostic method for detecting P. heveicola in planta. Specific primers (CPHF/CPHR) were designed based on sequence data of region of internal transcribed spacer (ITS1 and ITS4) of P. heveicola . The efficiency and specificity of CPHF/CPHR were established by PCR analysis of DNA from P. heveicola strains isolated from China and fungal isolates of other genera. A single amplification product of 318 bp was detected from DNA P. heveicola isolates. No amplification product was observed with any of the other fungal isolates tested. The specific primers designed and employed in PCR detected P. heveicola up to 3 pg from DNA isolated. This is the first report on the development of a species‐specific PCR assay for identification and detection of P. heveicola . Thus, the PCR‐based assay developed was very specific, rapid and sensitive tool for the detection of pathogen P. heveicola .